Hepatic Cerebroside Sulfotransferase Is Induced by PPARα Activation in Mice - Takefumi Kimura; Takero Nakajima; Yuji Kamijo; Naoki Tanaka; Lixuan Wang; Atsushi Hara; Eiko Sugiyama; Eiji Tanaka; Frank J. Gonzalez; Toshifumi Aoyama (PPAR Research)
Sulfatides are one of the major sphingoglycolipids in mammalian serum and are synthesized and secreted mainly from the liver as a component of lipoproteins. Recent studies revealed a protective role for serum sulfatides against arteriosclerosis and hypercoagulation. Although peroxisome proliferator-activated receptor (PPAR) α has important functions in hepatic lipoprotein metabolism, its association with sulfatides has not been investigated. In this study, sulfatide levels and the expression of enzymes related to sulfatide metabolism were examined using wild-type (+/+), Ppara-heterozygous (+/−), and Ppara-null (−/−) mice given a control diet or one containing 0.1% fenofibrate, a clinically used hypolipidemic drug and PPARα activator. Fenofibrate treatment increased serum and hepatic sulfatides in Ppara (+/+) and (+/−) mice through a marked induction of hepatic cerebroside sulfotransferase (CST), a key enzyme in sulfatide synthesis, in a PPARα-dependent manner. Furthermore, increases in CST mRNA levels were correlated with mRNA elevations of several known PPARα target genes, and such changes were not observed for other sulfatide-metabolism enzymes in the liver. These results suggest that PPARα activation enhances hepatic sulfatide synthesis via CST induction and implicate CST as a novel PPARα target gene.